Binary polarization pupil filter: Theoretical analysis and experimental realization with a liquid crystal display - Moreno, Ignacio (2006)
The Jones matrix formalism has been applied to evaluate the response of an optical system when a non-uniform polarizing pupil is introduced. With this formalism we analyze and experimentally demonstrate the properties of a binary polarization pupil filter having two regions with two orthogonal linear polarization orientations. We first study the case when no analyzer is placed behind the pupil filter, and both, the transversal and the axial behavior are described in terms of the intensity and the local state of polarization. Then it is shown how the response of the optical system can be easily changed through the orientation of an analyzer placed behind the pupil. We experimentally verified the theory using a twisted nematic liquid crystal display, which produces two orthogonal linear polarization states for two different addressed voltages.